Role of the preferred habitat availability for small shark (Mustelus schmitti) on the interannual variation of abundance in a large Southwest Atlantic Coastal System (El Rincón, 39°-41°S) - Jaureguizar, Andrés Javier (2016)
Description of habitat preferences in marine fishes is important in order to understand their spatial distribution and ecology, and are one of the first steps towards conservation. In this paper, we evaluate the influence of environmental conditions (temperature, salinity), location (latitude-longitude, depth), time (year) and availability of preferred habitat on the relative biomass of the narrownose smooth-hound shark (Mustelus schmitti) in El Rincón (∼38°-41°S < 50 m), Argentina. We used an extensive database of bottom trawl surveys conducted yearly during southern spring (November-December) between 1994 and 2012, containing 502 sampling stations where relative biomass, environmental variables and location are registered. Relative biomass was modeled using Generalized Additive Models (GAM) in which zeros observations were incorporated using a Tweedie distribution, and model selection was carried out using generalized cross validation values (CGV) and Akaike information criterion (AIC). The best models selected indicate that a combination of location (nearshore areas), depth (<30 m) and salinity (≤ 33.5) was significant in explaining relative biomass across time. In addition, the percentage of preferred habitat by M. schmitti, was also a significant predictor for relative biomass and was correlated to the main freshwater discharge previous to the fisheries survey. Discussion focused on understanding the spatial ecology of this species. We highlighted how environmental variables become a key issue to understand biomass indices derived from fishery-independent surveys.